2021
DOI: 10.1111/jce.15182
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of procedural efficacy, balloon nadir temperature, and incidence of phrenic nerve palsy between two cryoballoon technologies for pulmonary vein isolation: A systematic review and meta‐analysis

Abstract: Introduction In May 2020, a novel cryoballoon system (POLARx; Boston Scientific) became available for catheter ablation of atrial fibrillation (AF). The design of the cryoballoon is comparable to the Arctic Front Advance Pro (AFA‐Pro; Medtronic), but it is more compliant during freezing. We compared the procedural efficacy, biophysical parameters, and risk of phrenic nerve palsy (PNP) between the two cryoballoons. Methods Embase, MEDLINE, Web of Science, Cochrane, and Google Scholar databases were searched unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 24 publications
6
22
0
Order By: Relevance
“…No phrenic nerve palsy occurred in the POLARx group (0%) compared to two documented persistent phrenic nerve palsy events in the AFA group (<1%) (Table 6). These comparable and low phrenic nerve palsy rates are in line with other studies [15,17,[19][20][21]. Thus, further larger studies are certainly needed to elaborate potential benefits of the novel DMS.…”
Section: Safety Firstsupporting
confidence: 85%
See 2 more Smart Citations
“…No phrenic nerve palsy occurred in the POLARx group (0%) compared to two documented persistent phrenic nerve palsy events in the AFA group (<1%) (Table 6). These comparable and low phrenic nerve palsy rates are in line with other studies [15,17,[19][20][21]. Thus, further larger studies are certainly needed to elaborate potential benefits of the novel DMS.…”
Section: Safety Firstsupporting
confidence: 85%
“…In our study complication rates were very low (Table 6) with comparable results in the AFA and the POLARx group. This acts in concert with previous studies reporting initial experiences with the POLARx catheter under clinical conditions with low complication rates for CB-guided PVI [17,[19][20][21]23].…”
Section: Safety Firstsupporting
confidence: 74%
See 1 more Smart Citation
“…Preliminary data shows the POLARx balloon reaches lower nadir temperatures than the Arctic Advance balloon [ 17 ]. The POLARx balloon also takes longer to thaw, which may reduce early re-ablation of PVI before concomitant tissues are sufficiently warmed and therefore reduce the incidence of dose-dependent complications such as esophageal injury.…”
Section: The Boston Scientific Polarx Vs Medtronic Arctic Front Advancementioning
confidence: 99%
“…The European IDE trial reported only one incidence of transient phrenic nerve palsy and no other major complications [ 18 ▪ ]. A review of the few European studies on the POLARx did not demonstrate significant incidents of PNP compared to the Arctic Front Advance [ 17 ], despite the addition of the DMS.…”
Section: The Boston Scientific Polarx Vs Medtronic Arctic Front Advancementioning
confidence: 99%